Hyperbolic Lattice Boltzmann Method and Quantum Modelling of Nanostructures: A Numerical Framework for Femtosecond Laser Induced Periodic Surface Structures - Sudarto, Derren Audric; Noor, Ikhsan Mochammad (CV. Generasi Intelektual Digital, 2024)
This paper presents a numerical analysis of laser induced periodic surface structures (LIPSS) using lattice Boltzmann method. The Cattaneo-Vernotte hyperbolic heat conduction model is used to derive the hyperbolic lattice Boltzmann in order to consider the non-Fourier effect in conduction. A Gaussian ultrashort laser is induced on a thin film with varying length in the nanoscale. The energy transfer within the material is governed by the two temperature model which calculates the evolution of electron and lattice temperatures. The thermal and optical properties of the nanostructure is modelled based on quantum mechanics theory. The resultant nondimensional temperature and ablation profile are compared to experimental and other numerical methods data. Additionally, the effect of parallel computing is shown.